ASSOCIATION BETWEEN PERCEPTION OF CLINICAL LEARNING ENVIRONMENTS AND LEARNING APPROACH ON CLERKSHIP STUDENTS OF MEDICAL FACULTY - Bulan Kakanita Hermasari; Erinda Kusuma Wardani; Agus Jati Sunggoro (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2019)
Background: Learning environment is one parameter to evaluate the quality of learning. The learning approach reflects how a student learns in various situations that affect learning. This study aims to know the relationship between the perceptions of the learning environment and the learning approaches in the clerkship students of Medical Faculty.Methods: This research used an analytical observational method with cross-sectional technique. The sample selection technique used cluster sampling. Respondents consisted of 178 students from all clinical rotations. Each respondent was given two questionnaires to assess perceptions of the learning environment and learning approaches. Data were analyzed using contingency coefficient test.Results: Student perceptions of the learning environment show similar results between the number of clinical rotations that have the category of 'good but need improvement' (9 clinical rotations) and the 'many problems' category (9 clinical rotations). Most of the students (84.27%) used the in-depth learning approach, the remaining 10.67% used the strategic approach, and 5.06% used the surface approach. There was relationship between learning environment perception and learning approach with contingency coefficient value C = 0.312, and value p = 0,001 (p <0.05).Conclusion: There is a weak relationship between perception of clinical learning environments and learning approach on clerkship students of the medical faculty, University Sebelas Maret..